Electron flow stability in the gas filled diode - Pashchenko, A.; Ostroushko, V. (Вопросы атомной науки и техники, 2017)
For the electron fow in the short-circuited diode filled with gas, with taking into account the braking force proportional to velocity, the stationary modes and their linear perturbations are considered. The equation for increment of perturbation amplitude increase is obtained. The ranges of braking coefficient values are found, in which existence of stable or unstable stationary modes is possible. Для потоку електронів у короткозамкненому діоді, заповненому газом, з урахуванням гальмівної сили, пропорційної до швидкості, розглянуто стаціонарні режими та їхні лінійні збурення. Отримане рівняння для інкременту збільшення амплітуд збурень. Знайдено діапазони значень коефіцієнту гальмування, у яких можливе існування стійких або нестійких стаціонарних режимів. Для потока электронов в короткозамкнутом диоде, заполненном газом, с учетом тормозящей силы, пропорциональной скорости, рассмотрены стационарные режимы и их линейные возмущения. Получено уравнение для инкремента увеличения амплитуд возмущений. Найдены диапазоны значений коэффициента торможения, в которых возможно существование устойчивых либо неустойчивых стационарных режимов.